Intraosseous Hydatid cyst of sacrum and pelvic bone. An Uncommon Occurrence (Nepalese Journal of Radiology, 2021)
Skeletal hydatidosis results from deposition of the larval form of the Echinococcus, a genus of tapeworm. The incidence of bone disease is extremely low as most larvae are trapped by the liver and lung upon release of the embryo into the portal blood stream. Bone hydatid disease is often asymptomatic and its diagnosis is usually made at an advanced stage when lesions have become extensive. The interpretation of imaging studies can prove very confusing as there are no characteristic features and this often leads to misdiagnosis. We present a case of a 83 year-old man who was admitted to BPKIHS, Dharan complaining of pain and swelling in left hip.CT scan  showed lytic lesion in sacral vertebra involving  left sacroiliac joint and ilium and was falsely diagnosed as tuberculosis or  neoplastic in nature. The result of  FNAC concurred on an unexpected diagnosis of a hydatid cyst. This case illustrates that in the absence of  high index of suspicion for echinococcal infection, imaging findings of hydatid disease in bone mimic to those of other skeletal pathologies and can lead to misinterpretation.